DOI: 10.18174/583113
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the unexplored : Unravelling the cyto-nuclear interactions in Arabidopsis thaliana to improve photosynthesis

Abstract: In the previously described case of the PsbA-mediated resistance to atrazine in A. thaliana, it was found that the selection on this PsbA mutation was sufficiently strong, to ensure that the entire nuclear genome could hitchhike along with the PsbA mutation across the British Railroads (Flood et al., 2016a). This demonstrates how variation in the organellar genomes, can impose a selective pressure on nuclear genomes. Over time, such selection pressures can result in phenotypic variation that is dependent on sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 392 publications
0
4
0
Order By: Relevance
“…Nevertheless, also mitochondrial genes are known to play a role in photosynthesis (67). In the new cybrid panel, we found that the Staro-2 plasmotype induced cytoplasmic male sterility (CMS) due to a partially duplicated mitochondrial ORF (68). CMS is often associated with reduced mitochondrial respiration (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, also mitochondrial genes are known to play a role in photosynthesis (67). In the new cybrid panel, we found that the Staro-2 plasmotype induced cytoplasmic male sterility (CMS) due to a partially duplicated mitochondrial ORF (68). CMS is often associated with reduced mitochondrial respiration (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…Although a lot of studies have focused on the genetic variation in the mechanisms regulating the speed of photosynthetic induction or NPQ relaxation (Kaiser et al, 2019a;Tanaka et al, 2019;Murchie and Ruban, 2020;Long et al, 2022;Sakoda et al, 2022), less attention has been paid to the interaction between the diurnal change in light intensity and time of day of measurements. The quantitative trait locus (QTL) mapping of photosynthetic traits, including πœ™ 𝑃𝑆𝐼𝐼 and qE, revealed that the time of day, adaptation and duration of light period all influenced whether a QLT affects NPQ (Theeuwen, 2023). Understanding the effect of the diurnal light intensity profile on NPQ will help design experiments to study diurnal variation of NPQ and the underlying physiological and biochemical mechanisms.…”
Section: The Effect Of Diurnal Light Intensity Profile On Photoprotec...mentioning
confidence: 99%
“…The importance of growing plants in more realistic light intensity diurnal profiles in photosynthetic phenotypes studies was already raised (Mishra et al, 2016). Research on photosynthetic traits has been done in Arabidopsis plants grown in artificial phenotyping platforms in which the dynamics of light intensity and light fluxes can be adjusted very close to that of the natural light (Cruz et al, 2016;Theeuwen, 2023). Similar studies in species other than Arabidopsis are not reported yet.…”
Section: The Effect Of Diurnal Light Intensity Profile On Photoprotec...mentioning
confidence: 99%
See 1 more Smart Citation